On the transfer of skills skill in different conditions of motor activity - V.A. Zaporozhanov; T. Borachinski (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The aim of the study is a metric description of the transport of mobility in terms of kinesthesia in examined in a comprehensive registration block of six different motor coordination tasks. A total of 56 students in six different test tasks coordination complexity. The results of the initial control of processed statistically. Two calculated correlation matrix 6x6. The efficiency of use in subsequent statistical operations previously only justified, metrological reliability of the results. The transfer of skills in terms of agility kinesthesia found only in two exercises of this nature, explicable by common physiological mechanisms of regulation. The results of the study confirm the well-known knowledge of the complexity of mobility and contrary to some of the original authors of the possible use of a single universal control exercise - test for evaluation.